IMPLEMENTATION OF VALUE CHAIN AND MANAGEMENT CONTROL IN ORDER TO INCREASE COMPETITIVE ADVANTAGES (Study at PT Industri Marmer Indonesia Tulungagung) - Ditto Arief Wijaya (Fakultas Ilmu Administrasi Universitas Brawijaya, 2013)
The purpose of this study are knowing wheter Company applies the value chain for their business, knowing wheter Company applies the management control for their business, knowing the influence of value chain to competitive advantages, and knowing the influence of management control to competitive advantages. The results of the research showed that there was a double function in the organization structure, campany’s mission is the same with PT Gajah Perkasa Indonesia’s mission and the company’s goal does not show when this goal can be achieved, and company’s management control is good enough but some aspects need some improvement. The company’s competitive advantages can not be improved although the company’s management control is good. Based on the research about the organizational structure of the company for separation of finance and accounting department is needed, in the strategy formulation should be clear in company’s goal, and ongoing strategic analysis in the strategy implementation should be done in the right way such as mentions several criteria of worker, modificate the machine from mining, procesing and finished machine and serving segment that is less attractive to improve product differentiation. Keywords: organizational structure, strategy formulation, management control, value chain and competitive advantages